WAWASAN AL-QURAN TENTANG PRINSIP DAN ETIKA BISNIS - Supriadi, Akhmad (Jurnal Studi Agama dan Masyarakat, 2013)
Â Al-Qurâan, as the guidance of muslim in all age, included all aspects of life in it. It did not only talk about ritual teachings, but it also gave the followers the comprehensive guidance of how to interact with other people in social life and business and economic life. This article was aimed to explore Qurâanic terms, ethics, and principles in relation to business and economic issue. According to this research, these economic and business terms were mentioned frequently in different suras: al-bayâi, al-ribaâ, al-tijarah, al-adl, al-qisth, al-rizq, al-mal, etc. Based on the terms, the fundamental ethics, and the principles of Qurâan in business and economy, there were integration (tawhid), balance, justice, mutual trust and advantage, honesty, prime service, togetherness, social care and responsibility, hygiene and legality.